Densities, ultrasonic speeds, refractive indices, and COSMO analysis for binary mixtures of dichloromethane with acetone and dimethylsulfoxide at T = (298.15, 303.15, and 308.15) K - Nabi, Arshid; Zain, Sharifuddin Md; Jesudason, Christopher Gunaseelan (Taylor & Francis, 2018)
Experimental densities (ρ), ultrasonic speeds (u), and refractive indices (nD) of binary mixtures of dichloromethane (DCM) with acetone (ACT) and dimethylsulfoxide (DMSO) were measured over the whole composition range at T = 298.15, 303.15, and 308.15 K. From the experimental data, excess molar volume (VE), deviations in isentropic compressibility (Δks), deviations in intermolecular free length (ΔLf), deviations in refractive index (ΔnD), and deviations in ultrasonic speed (Δu) were calculated. Moreover, the Benson–Kiyohara theory was applied to the binary mixtures to obtain the theoretical Δks values. The COSMO calculations depending on density functional theory were utilized to estimate the σ-profiles for the DCM, ACT, and DMSO. The interpreted σ-profile trends were found supportive with the experimental findings. Applicability of different empirical and semi-empirical relations of refractive index data were tested against the measured results, and good agreement has been obtained. The possible results of intermolecular molecular interactions among mixture components were interpreted.